2017
DOI: 10.1186/s12913-017-2060-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between caregivers’ knowledge and care seeking behaviour for children with symptoms of pneumonia in six sub-Saharan African Countries

Abstract: BackgroundPneumonia is the main cause of child mortality world-wide and most of these deaths occur in sub-Saharan Africa (SSA). Treatment with effective antibiotics is crucial to prevent these deaths; nevertheless only 2 out of 5 children with symptoms of pneumonia are taken to an appropriate care provider in SSA. While various factors associated with care seeking have been identified, the relationship between caregivers’ knowledge of pneumonia symptoms and actual care seeking for their child with symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
3
31
0
2
Order By: Relevance
“…One qualitative study 25 revealed demandside barriers to healthcare utilisation in Nigeria, suggesting that costs, physical distance, cultural considerations, and knowledge of symptoms and warning signs might all play a role in delayed careseeking and could explain behaviours in other locations. In one study 26 of six countries in sub Saharan Africa, only 30% of care givers recognised fast breathing or difficulty in breathing as a symptom of LRI. Among several countries in western subSaharan Africa, the proportion of care givers who reported seeking treatment for symptoms of pneumonia ranged from 27·4% in Chad to 73·2% in Sierra Leone and was 41·9% in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One qualitative study 25 revealed demandside barriers to healthcare utilisation in Nigeria, suggesting that costs, physical distance, cultural considerations, and knowledge of symptoms and warning signs might all play a role in delayed careseeking and could explain behaviours in other locations. In one study 26 of six countries in sub Saharan Africa, only 30% of care givers recognised fast breathing or difficulty in breathing as a symptom of LRI. Among several countries in western subSaharan Africa, the proportion of care givers who reported seeking treatment for symptoms of pneumonia ranged from 27·4% in Chad to 73·2% in Sierra Leone and was 41·9% in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Among several countries in western subSaharan Africa, the proportion of care givers who reported seeking treatment for symptoms of pneumonia ranged from 27·4% in Chad to 73·2% in Sierra Leone and was 41·9% in Nigeria. 26 Appropriate care and treatment to protect against LRI mortality are important but the two risk factors responsible for the largest reduction in LRI mortality at the global level and for the largest prevention of incident episodes of LRI are Hib vaccine coverage and household air pollution. Vaccines have been an important part of LRI prevention in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 596 diarrheic children, only 196 (32.9%) were taken by their caregivers to health facilities. Parents with poor knowledge are unlikely to go to hospitals because there is a positive association between knowledge and care-seeking behavior [ 40 ]. The percentage of caregivers who knew home-based fluids for treating diarrhea was very low in similar studies from other developing countries [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found recognition of pneumonia by caregivers in low income countries to be poor [7]. Caregivers’ poor knowledge of the symptoms and danger signs of childhood pneumonia can also contribute to delays or failure to seek care [8,9]. Other factors such as distance to health care facilities and economic status can affect caregivers’ ability to seek care.…”
mentioning
confidence: 99%